Expression quantitative trait loci in long non‐coding RNA ZNRD1‐AS1 influence both HBV infection and hepatocellular carcinoma development. Issue 11 (11th August 2014) - Wen, Juan; Liu, Yao; Liu, Jibin; Liu, Li; Song, Ci; Han, Jing; Zhu, Liguo; Wang, Cheng; Chen, Jianguo; Zhai, Xiangjun; Shen, Hongbin; Hu, Zhibin
<x xml:space="preserve">Abstract</x> Zinc ribbon domain containing 1 (ZNRD1), cloned from human leukocyte antigen (HLA) region, may play integral roles in diverse processes including immune response against HBV infection and hepatocarcinogenesis. ZNRD1‐AS1 (ZNRD1 antisense RNA 1) may be an important regulator of ZNRD1. By bioinformatics analyses, we identified that several single nucleotide polymorphisms (SNPs) in ZNRD1‐AS1 may be expression quantitative trait loci (eQTLs) for ZNRD1. In this study, we hypothesized that these eQTLs SNPs in ZNRD1‐AS1 may influence both chronic HBV infection and hepatocellular carcinoma (HCC) development. We designed a case‐control study of 1300 HBV‐positive HCC patients, 1344 HBV persistent carriers and, 1344 HBV natural clearance subjects to test the associations of three ZNRD1 eQTLs SNPs (rs3757328, rs6940552 and, rs9261204) in ZNRD1‐AS1 with the risk of both chronic HBV infection and HCC. Logistic regression analyses in additive genetic model showed that variant alleles of all the three SNPs increased host HCC risk, whereas variant allele of rs3757328 was associated with HBV clearance. Moreover, the haplotype containing variant alleles of the three SNPs was significantly associated with both HCC development (adjusted OR = 1.18, 95% CI = 1.01–1.38, P = 0.035) and HBV clearance (adjusted OR = 0.83, 95% CI = 0.71–0.96, P = 0.013), when compared with the most frequent haplotype. In vitro experiments showed that ZNRD1 knockdown inhibited the expression of HBV mRNA and promoted proliferation of HepG2.2.15 cells. These findings suggest that ZNRD1 regulatory SNPs may be susceptibility makers for risk of both chronic HBV infection and HCC. © 2014 Wiley Periodicals, Inc.